Role of multiplex polymerase chain reaction using IS6110 and Protein b for the diagnosis of extra-pulmonary tuberculosis: North India - Kusum Sharma; Suma B Appannanavar; Manish Modi; Malkit Singh; Aman Sharma; Subhash Varma (Wolters Kluwer Medknow Publications, 2015)
Background: Prompt and accurate diagnosis of extra-pulmonary tuberculosis (TB) is highly challenging. Current conventional techniques lack sensitivity and are time-consuming. Here, we report our experience with multiplex polymerase chain reaction (MPCR) using two targets namely IS6110 and protein antigen b in the diagnosis of extra-pulmonary TB. Materials and Methods: A total of 150 patients of extra-pulmonary TB visiting tertiary care center in north India between September 2008 and December 2009 were included in the study. Sixty-six biopsy samples and 84 were body fluids from these patients were subjected for microscopy (Ziehl-Neelsen), culture on LJ medium and for Multiplex PCR using IS6110 and Protein b antigen. Results: Smear positivity was noted in 11 samples (7.33%), and LJ culture yielded Mycobacterium tuberculosis in 8 biopsies and 9 body fluids with overall positivity of 11.3%. The multi-targeted PCR could detect M. tuberculosis in a total of 112 samples. Of 112 positive samples, only Protein b band was detected in 7 samples and only IS6110 was detected in 5 samples. Overall Protein b, PCR could detect 71.33% of the cases, whereas IS6110 was positive in 66.6% of the cases. Overall the sensitivities of microscopy, culture, IS6110 PCR, Protein b PCR and MPCR were 7.33%, 11.3%, 66.67%, 71.3% and 74.6%, respectively. Thus by using more than two targets the sensitivity increased from 66.67% of IS6110 to 74.6% in MPCR. Conclusion: Multiplex polymerase chain reaction using IS6110 and Protein b antigen is a highly sensitive and specific tool in the diagnosis of pauci-bacillary conditions like extra-pulmonary TB.